GAMBARAN PERKEMBANGAN ANAK STUNTING PADA RENTANG USIA 24-36 BULAN DI PUSKESMAS OEMASI - Tat, Florentianus; Nugroho, Febtian Cendradevi; Pratama, Siti Ratna Putri; Bait, Maria Magdalena; Pujiyanti, Riny (Nursing Arts, 2023)
Stunting is a problem that is increasingly found, there are 195 million children living in poor and developing countries experiencing stunting. The incidence of stunting among children under five in Indonesia is 30.8% with the criteria of very short 11.5% and short 19.3%. The risk of malnutrition that can occur is developmental disorders in children. This study aims to obtain a description of the development of stunted children aged 24-36 months in the working area of the Oemasi Health Center, Kupang Regency. This study is a quantitative descriptive study, using the KPSP instrument. Sampling using total sampling technique. The sample size was 51 stunted children aged 24-36 months. Data analysis using descriptive frequency. This study shows that stunted children aged 24-36 months in the working area of Puskesmas Oemasi experience doubtful fine motor development (51.0%), doubtful gross motor (52.9%), doubtful speech and language (47.1%) and doubtful independence socialization (47.1%). The results of the study concluded that stunted children aged 24-36 months in the Oemasi Health Center Working Area experienced dubious development, meaning that development was not in accordance with age. Keyword: Stunting, Child Development